MANAGEMENT OF DETRUSOR SPHINCTER DYSSYNERGIA (DSD) IN A DOG - M. Shiju Simon; Chhavi Gupta; R. Ramprabhu; S. Prathaban (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A seven year old female Doberman dog was presented with the history of dullness, anorexia and dysuria for three days. Abdominal palpation revealed distended bladder, which was confirmed by plain radiography and ultrasonography on Neurological examination animal was found to be normal. On manual compression of the bladder urine was not evacuated, therefore by catheterization was performed and no obstruction was found; around three litres of urine was drained. The animal was treated with oral Diazepam, @ 0.04mg/kg, Prazosin, 1mg/15 kg and Bethanechol, @ 2mg/kg bd. wt. On fourth day of treatment, the animal was able to urinate normally and it was advised to continue the treatment for two weeks. The animal had an unevenful recovery.